1981
DOI: 10.1136/thx.36.3.194
|View full text |Cite
|
Sign up to set email alerts
|

Clotted false lumen: reappraisal of indications for medical management of acute aortic dissection.

Abstract: Evidence of a clotted false lumen in patients with acute aortic dissection has been considered to be a primary indication for medical rather than

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 7 publications
(4 reference statements)
0
3
0
Order By: Relevance
“…12,13 However, it has since been reported that thrombosed false lumen (or intramural hematoma) is not necessarily a factor of good prognosis, [14][15][16][17] because there were patients with thrombosed lumen who were first treated medically and then needed surgery during follow up, especially among those with Stanford type A dissection. In the present study, the status of false lumen was not the only variable that was an independent predictor of event.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 However, it has since been reported that thrombosed false lumen (or intramural hematoma) is not necessarily a factor of good prognosis, [14][15][16][17] because there were patients with thrombosed lumen who were first treated medically and then needed surgery during follow up, especially among those with Stanford type A dissection. In the present study, the status of false lumen was not the only variable that was an independent predictor of event.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that although thrombosis of the false lumen is in and of itself a good prognostic indicator, 27 it does not always prevent aneurysm formation and rupture, highlighting the need for close long-term surveillance in all cases. 28 In our institution, we treated 77 patients with type B aortic dissection during the same 7.5-year period mentioned above. Sixty-four (83%) had acute dissection (defined as treatment within 2 weeks of clinical onset).…”
Section: Chronic Aortic Dissectionmentioning
confidence: 99%
“…and Crawford [I 1].Several reports have been published on the subject of T-type dissections[12]; however, their precise clinical features -The actuarial survival curve in patients with Stanford type B dissection; a comparison of patients who had undergone surgery with those who were given no surgical intervention. The actuarial survival rates for patients with Stanford type B dissection were not significantly different.…”
mentioning
confidence: 99%